Permission to Say “Capitalism”: Principles for Critical Social Science Engagement With GGR Research - Hall, Stephen; Davis, Mark (Frontiers in Climate, 2021)
The grand scale of GGR deployment now necessary to avoid dangerous climate change warrants the use of grand interpretive theories of how the global economy operates. We argue that critical social science should be able to name the global economy as ‘capitalism’; and instead of speaking about ‘transforming the global economy’ as a necessary precondition for limiting climate change, instead speak about transforming, or even transcending, capitalism. We propose three principles are helpful for critical social science researchers willing to name and analyse the structural features of capitalism and their relation to greenhouse gas removal technology, policy and governance. These principles are: 1) Greenhouse Gas Removal technologies are likely to emerge within capitalism, which is crisis prone, growth dependent, market expanding. We use a broad Marxist corpus to justify this principle. 2) There are different varieties of capitalism and this will affect the feasibility of different GGR policies and supports in different nations. We draw on varieties of capitalism and comparative political economy literature to justify this principle 3) Capitalism is more than an economic system, it is ideologically and culturally maintained. Globally-significant issues such as fundamentalism, institutional mistrust, precarity and populism, cannot be divorced from our thinking about globally significant deployment of greenhouse gas removal technologies. We use a broad Critical Theory body of work to explore the ideational project of maintaining capitalism and its relation to GGR governance and policy.